ANALISIS INOVASI PELAYANAN PUBLIK RUMAH SEHAT LANSIA DI KOTA YOGYAKARTA - M. Rizki Pratama (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
The increasing population of the elderly people in Indonesia can have adverse impacts if not managed properly. However, only a few local governments are able to create policies that facilitate the health of the elderly. Yogyakarta City Government is able to implement innovative policies to accommodate the elderly through healthy elderly care (rusela). This research explains how the innovation process works in the midst of the lack of local government attention in improving the health of the elderly. This study uses a qualitative approach with research data obtained through secondary data and interviews. The results of this study explain that: first, the researcher found that the initiation of rusela emerged from collaboration between bureaucrats and practitioners, secondly the implementation of rusela could occur due to support from stakeholders, thirdly the promotion of rusela in order to remain sustainably obtained through internal and external promotion.